Pengaruh Kompetensi Pedagogik Guru Dan Iklim Sekolah Terhadap Motivasi Belajar Siswa Kelas VII Di SMP Terpada Az Zahra Desa Karangsambung Kecamatan Arjunawinangun Kabupaten Cirebon - Hasanudin Hasanudin (Peneliti.net, 2022)
The purpose of this study was to determine how much influence the teacher's pedagogic competence and school climate had on the learning motivation of eighth grade students of SMP Terpadu Az Zahra. The hypothesis of this research is that there is a positive influence of teacher pedagogic competence and school climate on learning motivation. This research was conducted using a correlational descriptive method, with the entire population of class VIII SMP Terpadu Az Zahra collecting 64 people. Because the population is relatively small, the authors use a saturated sampling technique. The technique of collecting data is by distributing questionnaires. Based on the results of the t-test of teacher pedagogical competence and school climate on student learning motivation, it was obtained that a significant value of teacher pedagogic competence was 0.015 <0.05, then Ho was rejected, meaning that teacher pedagogic competence had a positive effect on learning motivation. Then the significance value of the school climate obtained a significance value of 0.042 <0.05 then Ho is rejected, meaning that the school climate has a positive and significant effect on learning motivation.